Distortion correction for the orthogonally-splitting-imaging pose sensor. (June 2015) - Yang, Qian; Sun, Chang-ku; Wang, Peng; Li, Wen-qiang; Liu, Xin-tong
Abstract: The orthogonally-splitting-imaging pose sensor utilizes not only large field of view spherical lenses but also two sets of cylindrical ones to realize the high-speed, high-precision and wide-field pose measurement. Notable distortion, however, results from the wide-field lenses at the same time. Therefore, to obtain the best performance of the camera model, a distortion correction method is proposed in this paper, which combines the advantages of the high-stability of the Least Square fittings based on the orthogonal polynomials and the independence of the distortion correction based on the cross-ratio invariability. In this way, the ill-conditioned fitting matrix as well as the iteration and optimization procedures in solving extrinsic and intrinsic parameters can be avoided. Due to the wide fitness of the cross-ratio invariability and the orthogonal polynomials, this distortion correction technique is also suitable to other optical set up with different imaging structure. The experiment results that the corrected grids have superior precision and reliability with their original slopes demonstrate that the distortion model on the basis of orthogonal polynomial is validated and that the distortion correction is effective. Highlights: The orthogonal-splitting-imaging pose sensor is built to realize pose measurement. A synthesized nonlinear distortion correction method is put forward. The distortion correction method is of high stability and wide application range.